Analisis Strategi Public Relations Melalui Instagram dalam Meningkatkan Citra Layanan PaxelMarket - Nabila Gwen Aalia; Andina Dwifatma (Jurnal InterAct, 2025)
The rapid development of digital technology, accompanied by the increasingly competitive growth of e-commerce in Indonesia, has significantly transformed consumer behavior, particularly in online shopping activities. This transformation not only simplifies transaction processes but also shapes new expectations regarding speed, security, and service quality. In this context, the need for reliable logistics services has become increasingly crucial, especially for the delivery of frozen food and fresh products that require special handling to maintain their quality until they reach consumers. This study aims to analyze the public relations strategy implemented by PT Paxel Algorita Unggul through its Instagram account @paxelmarket in an effort to enhance the service image of PaxelMarket in the public’s perception. The research employs a qualitative approach with a descriptive method to gain an in-depth understanding of the communication practices applied. Data collection techniques include semi- structured interviews with internal company representatives, unstructured interviews with consumers, observations of Instagram content, and analysis of relevant supporting documents. The theoretical framework of this study encompasses the concepts of public relations strategy, social media utilization, and image formation. The analysis focuses on Cyber Public Relations practices, particularly in managing organic content, building engagement with the public, and communicating the service value of PaxelMarket as an artisan food marketplace. The findings indicate that PaxelMarket’s public relations strategy is both value-driven and relational, as reflected in content-based education, visual curation of MSME products, and responsive two-way communication. These strategies contribute to building a positive service image in the digital space. However, public understanding of PaxelMarket’s positioning as an artisan marketplace still needs to be strengthened to ensure that brand differentiation is consistently embedded in consumers’ minds.